Virtual teams: a literature review - Ebrahim, Nader Ale; Ahmed, Shamsuddin; Taha, Zahari (American-Eurasian Network for Scientific Information, Jordan, 2009)
In the competitive market , virtual teams represent a growing response to the need for fasting time-to- market, low-cost and rapid solutions to complex organizational problems. Virtual teams enable organizations to pool the talents and expertise of employees and non-employees by eliminating time and space barriers . Nowadays, companies are heavily investing in virtual team to enhance their performance and competitiveness. Despite virtual teams growing prevalence, relatively little is known about this new form of team. Hence the study offers an extensive literature review with definitions o f virtual teams and a structured analysis of the present body of knowledge of virtual teams. First, we distinguish virtual teams from conventional teams , different types of virtual teams to identify where current knowledge applies. Second, we distinguish what is needed for effective virtual team considering the people, process and technology point of view and underlying characteristics of virtual teams and challenges they entail. Finally, we have identified an d extended 12 key factors that need to be considered, and describes a methodology focused on supporting virtual team working, with a new approach that has not been specifically addressed in the existing literature and some guide line for future research extracted.